Modernização da agricultura no distrito de Monapo em Moçambique no contexto de redefinição da geopolítica da fronteira agrícola mundial entre 2004 a 2017 - Macaringue, Ernesto Jorge (2018)
The Mozambican economy relying on donations, credits and foreign investment is contradictory, ambiguous and unstable. The State as the main political and territorial actor has been made concessions of the country’s natural resources without a minimum respect of its citizen’s autonomy. Taking in consideration the way the land is administered in Monapo district, there is reason to affirm the Government is careless about its citizen’s wellbeing. In the name of development efforts, the Government of Mozambique and bilateral partners take advantage of the most human sensitive aspects such as hunger, for instance, to force citizens to adopt suffocating lifestyles that has an effective connection with the global geopolitical system, faltering the self-determination of the citizens. Taking in account that the references for development are not static, the idea of development is very difficult to achieve in the modern complexity world societies in which Mozambique is present as periphery. The financial resources spent in the name of fighting hunger and modernisations are nothing more than manoeuvres and new strategies to subdue the citizens through financial capital. Entitled “Agriculture modernisation in Monapo district the geopolitics redefinition of the world agricultural frontier between 2004 and 2017”, this research discusses agricultural modernisation in Mozambique. As mentioned above, Mozambique still subjected to a situation of poverty. Due to the Government interventions, there is expropriation of country’s natural resources, mainly, the land belonging to peasants and there is no one who protects their rights. In 2009, forty countries that command the world-modern system or capitalist world economy trying to show “civility”, established an agreement that was unfolded in “New Alliance for Food and Nutrition Security for African countries”, in which Mozambique is contemplated. The research problem lies on the view that under the “hunger geopolitics”, development corridors, many of which were conceived during colonisation era, reappear as new opportunities and projects for agribusiness investments. The Monapo district, in Nampula, with other several districts of Nampula, Zambézia and Niassa, located in the Nacala corridor, are in the spot of foreign investors, who are looking for land for commodities production, as well as for conversion of peasant’s systems in production systems linked to agribusiness. The implementation of this project is coordinated by the Government of Mozambique with bilateral partners through the Triangular Cooperation Program between Brazil, Japan and Mozambique for the Development of Agriculture in the Tropical Savannas of Mozambique - ProSAVANA-JBM. Based on Critical Geography, this research discusses the territoriality of capital masked in technical assistance to overcome food insecurity. Under the territorial assumption that the territorial changes, taking place in the Nacala Corridor, afoot in a cross-linkage between the world, national and local scales are modifying community life relations and arising several issues involving land, work and modes of life, a set of methodological procedure were decisive for accomplishment of the research, namely: literature review, field work, interviews and workshops.